The moderating influence of instructional intensity and word type on the acquisition of academic vocabulary in young English language learners - August, Diane; Artzi, Lauren; Barr, Christopher; Francis, David (Reading & writing, 2018)
This study used a within-subjects design to explore two instructional conditions for developing vocabulary in second-grade Spanish-speaking English learners (ELs)—extended instruction and embedded instruction implemented during shared interactive reading. Words assigned to the extended condition were directly taught using a multifaceted approach that included visuals, bilingual definitions, examples, spelling, and partner-talk about the words’ meaning. Words assigned to the embedded condition were taught solely through brief definitions to embedded text, writing activities, and songs. In the control condition students heard the target words read aloud during shared interactive reading but without definitions or direct instruction. The study also explored the interaction between instructional condition and word type. Four types of words—abstract cognates, abstract noncognates, concrete cognates, and concrete noncognates—were randomly assigned to each condition. Nine teachers in four schools and 187 second-grade ELs participated in this within-subjects intervention, which took place in transitional bilingual classrooms. Findings indicated that across all word types, both extended and embedded instruction were more effective than the control condition in helping ELs acquire vocabulary. Findings also indicated that extended instruction was more effective then embedded instruction for all word types except concrete cognates suggesting that these young Spanish-speaking ELs were advantaged by word knowledge in their home language. Finally, while embedded instruction was less effective than extended instruction, it was much more effective than a control condition. Embedded instruction takes significantly less preparation and instructional time than extended instruction, offering teachers a practical way to teach more vocabulary to ELs.